Method validation and dissipation kinetics of four herbicides in maize and soil using QuEChERS sample preparation and liquid chromatography tandem mass spectrometry. (1st January 2016) - Pang, Nannan; Wang, Tielong; Hu, Jiye
Highlights: Liquid chromatography tandem mass spectrometry with modified QuEChERS was developed. Satisfactory recoveries of four herbicides were between 80% and 110%. Dissipation kinetics study was conducted under open field conditions at two sites. The rapid half-lives of four herbicides were between 0.6 d and 3.6 d. The residues in two water dispersible granules were below maximum residue limits. Abstract: A versatile liquid chromatography tandem mass spectrometry method with modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) sample preparation was developed for the determination of rimsulfuron, mesotrione, fluroxypyr-meptyl, and fluroxypyr. By adjusting the amount of graphitized carbon black, the herbicide analytes could be quantified with satisfactory recoveries in the range of 80–110%. A dissipation kinetics study conducted under open field conditions at two sites during 2014 showed first order equations with half-lives between 0.6 d and 3.6 d, illustrating an appropriate degree of stability and safety. The dissipation kinetics were different in the different matrices. Although the herbicides had higher initial residues in straw than those in soil, they degraded faster in straw. The terminal residues for the herbicides formulated in two water dispersible granules were all below maximum residue limits. These results not only gave insights about the analytes but also contributed to environmental protection and food safety.